EFFECTS OF AUTOMATION AND ELECTRONIC DEVICES ON BOARD AIRCRAFT ON PILOT SKILLS, TRAINING REQUIREMENTS AND FLIGHT SAFETY - Daniela Ficova; Benedikt Badanik; Andrej Novak; Alena Novak-Sedlackova; Marek Turiak (Zeszyty Naukowe Wyższej Szkoły Finansów i Prawa w Bielsku-Białej, 2016)
The present and future challenges of commercial air transport industry require maintaining growth trends in air traffic and at the same time easing congestion in the skies without compromising high safety standards. This all leads to natural evolution of the aircraft cockpit environment. The progress starts now with implementation of headup displays, airport moving maps, interactive electronic checklists, enhanced vision using infrared cameras to enable night time vision and synthetic 3-D vision systems. In the future, technology development will continue with I4D operations, digital taxi realtime uplink of the cleared taxi route via Controller-Pilot Data Link Communication and much more. These modern cockpit features and their necessary future upgrades enable pilots to capitalize on their strengths and help them manage their weaknesses. Information from these systems are presented to the pilots in transparent manner which makes their decision-making process more efficient and safer, especially under stress. Taking into consideration future trends in the cockpit environment, the growth of the air transport and safety requirements, it is necessary to review the role of pilots. Aviation is a sphere where progress and continuous innovation is inevitable. Therefore, it is necessary to keep up with the evolution and adapt also the pilot training and education. Many major world top rated airlines have already implemented for example evidencebased trainings as they realized that the role of the pilot in the cockpit is changing. The basic pilot skills are essential but in today’s air transport operation we also need to take into account that pilots need to have certain managerial skills and therefore balance the training accordingly to make it more efficient. Whether we like it or not, the times of visual approaches and manual flying, especially in big commercial operations, are slowly disappearing. We need to understand this progress and adjust the structure of the pilot training accordingly to be able to deliver the best level of safety efficiency. The paper also deals with the use of portable multimedia devices for VFR flights. It explains the basic terms concerning the use of portable electronic devices on-board aircraft. It analyses the relevant international and national legislation for the use of portable electronic devices on-board aircraft. It includes a survey of the available devices, accessories and software on the market. An analysis and comparison of the devices, based on their technical specifications is included as well. The paper also deals with various aspects of the use of portable multimedia devices for a flight school. It reviews the whole process of selecting a suitable operating system, device, accessories and software with an example of calculation of the required financial expenses. A comparison of the devices based on the battery life in relation to the selected aircraft is also included. Furthermore, the paper considers the mounting options of the devices in the cockpit, points out to required changes in the operational procedures within the flight school and highlights the potential assets which application of portable electronic devices brings.